Analytical modeling of mixed-Mode bending behavior of asymmetric adhesively bonded pultruded GFRP joints. (October 2015) - Ševčík, Martin; Shahverdi, Moslem; Hutař, Pavel; Vassilopoulos, Anastasios P.
Highlights: An analytical method for fracture behavior modeling of asymmetrical joints. Theoretical calculation of the SERR at the crack tip. Method for the optimization of the laminate stacking sequence. Good agreement with experimental results. Abstract: This paper presents a semi-analytical methodology for the fracture mechanics assessment of asymmetric adhesively bonded composite joints. The method is based on the classical lamination theory, the simple beam theory and the extended global method. Experimental results obtained from quasi-static mixed-Mode bending (MMB) tests of adhesively bonded glass fiber reinforced polymer (GFRP) laminates were used for the validation of the introduced methodology. The main advantage of the proposed methodology is the ability of taking into account the fiber bridging effects as well as the arbitrariness of the adherend stacking sequence in a distance from the crack propagation path.